Postcolonial identity in contemporary English literature - Wulandari, Ika (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study examines the construction of postcolonial identity in contemporary English literature by employing a qualitative descriptive approach through close textual analysis. Focusing on selected literary works by postcolonial authors, the research explores how identity is represented as fluid, hybrid, and continuously negotiated within narratives shaped by migration, diaspora, and cultural displacement. Drawing on postcolonial theory, particularly the concepts of hybridity, otherness, and the “third space,” the analysis reveals that literary texts portray identity not as a fixed essence but as a dynamic process influenced by historical colonial legacies and contemporary global conditions. The findings indicate that experiences of diaspora and linguistic negotiation play a significant role in shaping postcolonial subjectivity, enabling characters to construct adaptive and plural forms of belonging. By integrating theoretical perspectives with close textual reading, this study contributes to English literary scholarship by reaffirming the relevance of postcolonial theory in interpreting contemporary literary representations of identity in a globalized world.